APLIKASI PERPUSTAKAAN BERBASIS WEB PADA SMP SWASTA PAB 9 DALAM PENINGKATAN PELAYANAN DAN STRUKTUR PERPUSTAKAAN - Putra, Randi Rian; Putra, Eka (Seminar Nasional Sosial Sains dan Teknologi Halal; 2021, 2022)
With the development of technological advances that greatly affect the development of information in an educational or academic field and in various other fields, one of which is the selection of student councils in schools during the covid 19 pandemic. The election of student council presidents is something we often do in junior high and high school but because it is still manual, often slows down the process of selecting the student council president. During the pandemic, the teaching and learning process will continue to be carried out online or online as well as the selection of the student council chair and his deputy, SMP Swasta PAB 9 Klambir Lima is a high school that wants to realize the technology development process to improve quality and quality. Therefore, the author wants to build a website-based online system, in order to make it easier for employees and students at SMA Negeri 1 Tarutung to speed up the processing of data on the results of the vote. In order to be easily accessed by other teachers and students to elect the student council chair, anywhere and anytime the SMP Swasta PAB 9 Klambir Lima can access this system as long as it is connected to the internet.